Original paperWeight reduction decreases NT-proBNP levels in obsese coronary patients with chronic diastolic heart failure - Cocco, Giuseppe; Chu, David (Archives of Medical Science, 2007)
Introduction: This study was designed to evaluate the effect of weight reduction on NT-proBNP levels in hypertensive obese patients with chronic diastolic heart failure (DHF). Obesity exerts a negative impact on the cardiovascular system and a weight reduction improves pathological changes. Circulating levels of NT-proBNP reflect left ventricular diastolic wall stress and are strongly related to mortality and treatment success in heart failure. Material and methods: Thirty-eight hypertensive obsese patients with stable DHF were enrolled in a 6 months diet counseling program aimed to achieve a >5 kg weight reduction. Thirty-two patients with the same cardiac pathology who were unwilling to adhere to the diet were used as a control group. Blood sampling for measurement of NT-proBNP and other laboratory values, functional assessment, 6-minute walk testing, cycloergometry, and echocardiography were obtained at entry and after 6 months. Results: In hypertensive obese patients with symptomatic DHF, a 7 kg weight and body mass index (BMI) reduction induced a fall in circulating levels of NT-proBNP, reflected by an improved diastolic dysfunction and a significant increase in the walking distance. The improvement was achieved without a negative impact on left ventricular compliance and remodeling. Conclusions: Weight reduction improved the cardiac function in patients being treated concurrently with modern antihypertensive drugs. The effect of the cardiac improvement was comparable to that seen with pharmacological treatment programs. This supports the need to implement a weight reduction in obese hypertensive patients with chronic DHF.